Current practice of autologous hematopoietic progenitor cell mobilization in adult patients with multiple myeloma and lymphoma: The results of a survey from Turkish hematology research and education group (ThREG). Issue 6 (December 2017) - Tekgündüz, Emre; Demirkan, Fatih; Vural, Filiz; Göker, Hakan; Özdoğu, Hakan; Kiki, İlhami; Aydoğdu, İsmet; Kaynar, Leylagül; Erkurt, Mehmet Ali; Çağırgan, Seçkin; Beşışık, Sevgi; Dağdaş, Simten; et al.
Abstract: Autologous hematopoietic cell transplantation (AHCT) is an established treatment option for adult patients presenting with multiple myeloma (MM), Hodgkin lymphoma (HL) and various subtypes of non-Hodgkin lymphoma (NHL) in upfront and/or relapsed/refractory disease settings. Although there are recently published consensus guidelines addressing critical issues regarding autologous hematopoietic progenitor cell mobilization (HPCM), mobilization strategies of transplant centers show high variability in terms of routine practice. In order to understand the current institutional policies regarding HPCM in Turkey and to obtain the required basic data for preparation of a national positional statement on this issue, Turkish Hematology Research and Education Group (ThREG) conducted a web-based HPCM survey. The survey was designed to include multiple-choice questions regarding institutional practice of HPCM in adults presenting MM, HL, and NHL. The representatives of 27 adult HCT centers participated to the study. Here we report the results of this survey shedding light on the real-world experience in Turkey in terms of autologous HPCM mobilization strategies in patients presenting with MM and lymphoma.